PEMETAAN KEMAMPUAN KOGNITIF PESERTA DIDIK SMP NEGERI DI SURABAYA: STUDI CROSS-SECTIONAL SURVEY DALAM BINGKAI PEMBELAJARAN MENDALAM - Bagus Ramadhan, Rafli; Hidayati, Siti Nurul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the issue of low cognitive ability among Indonesian students, particularly in the context of deep learning implementation in junior high schools. The research aims to analyze the cognitive abilities of students in Surabaya public junior high schools based on three main indicators: understanding, applying, and reflecting. This study employs a quantitative approach using a cross-sectional survey design involving 68 students from grades 7, 8, and 9. Data were collected through a 12-item multiple-choice test developed according to deep learning cognitive indicators and analyzed using descriptive statistics with JASP software. The results indicate that the applying indicator achieved the highest mean score (43.75), followed by understanding (40.44), while reflecting showed the lowest mean (30.88). These findings suggest that students are relatively better at applying knowledge than understanding concepts deeply or engaging in reflective thinking. Furthermore, variations across grade levels show different cognitive patterns, with grade 9 students demonstrating improved understanding compared to lower grades. Gender-based analysis reveals no significant difference in central tendency, although female students show greater variability in performance. Overall, the study highlights the need to strengthen reflective thinking skills to achieve a more balanced cognitive development aligned with deep learning principles.